Regulation Implementation of The Regional Spatial Planning for Majalengka District in 2011-2031 - Khoirunnisa Hanifah; Endang Sumantri; Cecep Darmawan (Jurnal Civicus, 2021)
Regional spatial planning is one of the most important parts of a city development process because regional spatial planning is an effort to determine the direction or vision of the city. The implementation of Regional Regulation No. 11 of 2011 concerning Spatial Plans for Majalengka Regency for 2011-2031 is no longer in line with the initial goal of realizing Majalengka Regency as a productive, competitive and sustainable agribusiness, tourism and industrial area. Therefore, researchers conducted research by examining the implementation of Regional Regulation No. 11 of 2011 concerning Spatial Planning for the Majalengka Regency Region for 2011-2031 which regulates spatial planning for the Majalengka district area. This study uses a qualitative descriptive method and data collection techniques using observation, interviews, and documentation. The results obtained from the research are that the implementation of this Regional Regulation is not carried out properly because it is no longer appropriate and needs to be revised. Overall, this review provides a reference point regarding the application of regional regulations for further research by identifying the implications of these regulations which can be seen from the aspect of community participation in showing their enthusiasm for the issuance of these regional regulations.